Peningkatan Pengetahuan Mengenai Kebersihan Selama Menstruasi pada Remaja Putri - Maharani, Sri; Hayati, Fatihatul; Sinulingga, Selpyani (Prosiding Seminar Kesehatan Nasional, 2023)
The menstrual cycle is the first part of reproductive health in young women. The problem that often arises related to reproductive health in adolescents is not being able to apply how to care for the reproductive parts, especially during menstruation. According to the BKKBN, low knowledge about reproductive health will enable women not to practice hygiene during menstruation which can endanger their own reproductive health. The habit of maintaining cleanliness, especially in the reproductive area, is the beginning of efforts to maintain health. Where during menstruation, the blood vessels in the uterus open so it is very easy to get infections. Personal hygiene during menstruation can be done by changing sanitary napkins every 2 hours or 3 to 4 times a day. Sanitary napkins should not be worn for more than six hours or should be changed as often as possible when they are full of menstrual blood to avoid infection. This community service is carried out by giving pretests to female students before and posttests after counseling. The results of the counseling showed that there was an increase in students' knowledge regarding hygiene during menstruation among young women at Al-Falah Islamic High School, Jambi City.